2020
DOI: 10.1002/jbm.a.37060
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion decellularization of porcine esophagus: Study of two processing factors affecting the folded mucosal structure of the esophageal scaffold

Abstract: Acellular scaffolds from decellularized donor organs are showing promising clinical results in tissue and organ repair and regeneration. A successful decellularization process is determined by (a) its capability to decellularize complete organs of large animals, (b) retention of the extracellular matrix (ECM) structures and morphologies, and (c) minimal loss of ECM proteins. In this study, porcine esophagi were perfused in full thickness with 0.25% w/v sodium dodecyl sulfate at perfusion rates 0.1–0.2 ml/min f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Tissue swelling after alkaline treatment and detergent perfusion are adequate to meet with two of the commonly accepted metrics of decellularization, that is, the lack of cell nuclei stained with the H&E protocol and the residual amount of DNA. Effective tissue decellularization and prevention of unfolding of the complaint mucosa are consistent with the perfusion method applied to the esophagus 7 . Meanwhile, the modification of the DSC traces after tissue decellularization is consistent with the necessary balance between the selected methods/agents with the characteristics of the resulting matrix; the presence of the denaturation peak suggests preservation of collagen stability.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Tissue swelling after alkaline treatment and detergent perfusion are adequate to meet with two of the commonly accepted metrics of decellularization, that is, the lack of cell nuclei stained with the H&E protocol and the residual amount of DNA. Effective tissue decellularization and prevention of unfolding of the complaint mucosa are consistent with the perfusion method applied to the esophagus 7 . Meanwhile, the modification of the DSC traces after tissue decellularization is consistent with the necessary balance between the selected methods/agents with the characteristics of the resulting matrix; the presence of the denaturation peak suggests preservation of collagen stability.…”
Section: Discussionsupporting
confidence: 65%
“…A second perfusion was applied to samples (sodium deoxycholate 4% in PBS, 2×, RT) during 1.5 h for 1 day esophagus or 2.5 h for 21 or 45 h esophagus, followed by a washing (PBS, 4°C, overnight). The perfusions were carried out in horizontal position 7 Third step: nucleases treatment .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium dodecyl sulfate (SDS) is one of the most effective and commonly used surfactants to decellularize tissues and organs. Our previous study confirmed that SDS effectively decellularized porcine esophagi [6]. However, the real-time interactions between SDS and cells during decellularization are not well understood, except that the process is very rapid.…”
Section: Introductionmentioning
confidence: 70%
“…The SDS solution was prepared in PBS (Sigma-Aldrich, Saint Louis, MO, USA) at a concentration of 200 ppm (w/v). The SDS concentrations used in organ decellularization typically ranged between 1000 to 100,000 ppm [6,15,16]. However, at these SDS concentrations, their effects on the cells were too rapid to be imaged using our current QPI setup.…”
Section: Sds Solution Preparationmentioning
confidence: 99%